Motivasi Belajar Bahasa Arab Siswa Kelas III Ikhwan SDIT Ar-Ra’uf Bandar Lampung Tahun Pelajaran 2021/2022 - Nadia Kurniawati; Ahmad Hadi Setiawan; Muhammad Singgih (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2022)
This research was carried out against a background of low interest in learning and lack of motivation in learning Arabic in third grade ikhwan students at SDIT Ar-Ra'uf Bandar Lampung which is characterized by being easily bored in learning and there are still many students whose Arabic learning outcomes are incomplete. The aims of this study were (1) to find out how the third grade students' motivation at SDIT Ar-Ra'uf Bandar Lampung students learn Arabic, (2) to find out the factors that influence learning motivation. The type of research used in this research is qualitative descriptive. The subjects of this study were the third grade students of SDIT Ar-Ra'uf Bandar Lampung, which consisted of 26 male students. The results of this study indicate that (1) the learning motivation of class III students at SDIT Ar-Ra'uf with the result that 63% of students are motivated and 37% of students are not yet motivated so that it can affect students' Arabic learning outcomes, (2) learning motivation can be influenced by 2 factors namely, internal and external factors.